2011
DOI: 10.1002/asi.21553
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of public library users' digital preservation practices

Abstract: This research investigated preservation practices of personal digital information by public library users. This qualitative study used semistructured interviews and two visual representation techniques, information source horizons and matrices, for data collection. The constant comparison method and descriptive statistics were used to analyze the data. A model emerged which describes the effects of social, cognitive, and affective influences on personal preservation decisions as well as the effects of fading c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…265-266). This typology has been explored in other studies of adults' ELIS activities (Copeland, 2011;Davenport, Richey, & Westbrook, 2008), mainly using interview methods to examine participants' views and perspectives. In order to extend the current analysis to examine this typology, interviews with children or other techniques designed to capture their personal outlooks on their ELIS activities, would be required.…”
Section: Resultsmentioning
confidence: 99%
“…265-266). This typology has been explored in other studies of adults' ELIS activities (Copeland, 2011;Davenport, Richey, & Westbrook, 2008), mainly using interview methods to examine participants' views and perspectives. In order to extend the current analysis to examine this typology, interviews with children or other techniques designed to capture their personal outlooks on their ELIS activities, would be required.…”
Section: Resultsmentioning
confidence: 99%
“…Studies involving personal information management have found that most individuals treat all their digital content the same, regardless of value [1]. For example, many individuals report backing all their content up rather than just items they deem important.…”
Section: Discussionmentioning
confidence: 99%
“…One begins to wonder if any of this content is worthy of preservation. Research has found that individuals share digital content that is valuable to them for a variety of reasons [1,2]. However, is it valuable to others?…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the location or media type of their content, the organisa tional tools available to users are familiar: filenames, folders and some dedi cated applications (e.g. iTunes) [1].…”
Section: Related Workmentioning
confidence: 99%